Infrared, X-Ray and Thermal Studies of Magnesium Soaps - Singh, Chitra; Upadhyaya, S.K. (Asian Journal of Chemistry, 2010)
The IR results indicate that the fatty acids have dimeric structure achieved through hydrogen-bonding between the carboxyl groups of two fatty acid molecules whereas the magnesium soaps possess ionic character; x-ray analysis showed that magnesium soaps have single layer structure with molecular axes slightly inclined to the basal plane. The results of thermogavimetric analysis were explained by using Freeman Carroll and Horowitz-Metzger's equations to calculate the energy of activation and order of decomposition reaction.